Educated Yet Underutilised: A Qualitative Inquiry Into The Experiences And Challenges Of Unemployed And Underemployed Graduates In The Or Tambo District Municipality, South Africa - Zenzo, Babalo; Mefi, Nteboheng Patricia; Konyana, Samkele; Asoba, Samson Nambei (Journal of Ecohumanism, 2025)
Background: In South Africa, graduate unemployment and underemployment continue to be major issues, especially in rural areas like OR Tambo district. Many graduates find it difficult to find fulfilling work despite the growth of higher education, which has far-reaching socioeconomic and psychological repercussions. Rural prospects were restricted by structural impediments, and these issues are made worse by the discrepancy between academic preparedness and job market expectations. Aim: To investigate the experiences, perceptions, and challenges of unemployed and underemployed graduates in the OR Tambo District, with a view to identifying potential strategies for improving graduate employability. Setting: The research was conducted in the OR Tambo District Municipality, located in the Eastern Cape Province of South Africa. The district is characterised by high unemployment levels, socio-economic inequalities, and rural underdevelopment, making it an ideal setting for examining graduate unemployment and underemployment in context. Methods: The study employed a qualitative research approach situated within an interpretivist paradigm, using a phenomenological design to capture participants lived experiences. Data were collected using a semi-structured online interview guide and was distributed via WhatsApp to graduates from universities and TVET colleges residing in the OR Tambo district. A purposive and snowball sampling strategy was used until data saturation was reached. Thematic analysis, guided by Braun and Clarke’s framework, was employed to identify and interpret emerging themes. Results: Four major themes emerged from the findings: (1) ongoing structural barriers to employment, such as nepotism, the "experience trap," and a lack of job opportunities in rural areas; (2) the significant social, economic, and psychological effects of unemployment, such as stress, financial strain, and a decreased sense of self-worth; (3) coping mechanisms, such as informal entrepreneurship, additional education, and reliance on social and spiritual support networks; and (4) recommendations from graduates that place a strong emphasis on mentorship, organised placement programs, entrepreneurship support, and tighter ties between the government, universities, and industry. Conclusion: The study emphasises the intricate interactions between personal, societal, and structural elements that influence graduate unemployment in rural South Africa. Multi-stakeholder initiatives are called for, such as structural changes to hiring procedures, targeted job creation in rural areas, increased assistance for graduate entrepreneurship, and better matching the demands of the labour market with higher education. Contribution: This study adds to discussions on graduate unemployment from an ecohumanist standpoint by highlighting the experiences of graduates in the OR Tambo District and highlighting the ethical and social justice aspects of employability. In addition to adding value to scholarly discussions, the findings give employers, higher education institutions, and policymakers useful information on how to increase community resilience and promote graduate involvement in the workforce.